DEVELOPMENT AND QUALITY OF SWEET MAIZE INOCULATED WITH DIAZOTROPHIC BACTERIA AND TREATED THIAMINE - Vendruscolo, Eduardo Pradi; Siqueira, Ana Paula Silva; Furtado, João Paulo Marques; Campos, Luiz Fernandes Cardoso; Seleguini, Alexsander (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The insertion of technologies that help to maintain or increase the productivity and quality of agricultural products is highly important in the face of the challenges for the generation of more sustainable farming systems. Thus, the objective of this work was to evaluate the biometric and post-harvest characteristics of sweet maize under inoculation with Azospirillum brasilense and different doses of thiamine applied by seed treatment. The experiment was conducted in a factorial scheme (2 x 4) and the composition of the treatments was the combination of the presence or absence of the Azospirillum brasilense and different doses of thiamine (0, 15, 30 and 45 mg kg-1). Were evaluated the grain yield, ear weight with and without the straw, straw weight, straw number, ear diameter, number of grain rows per ear, number of grains per row, number of grains per ear, soluble solids, titratable acidity and ratio. When isolated, the inoculation of sweet maize seeds with the Azospirillum brasilense improves ears biometric and quality characteristics and the application of thiamine as seed treatment, up to the dose of 25.27 mg kg-1, improves the biometric characteristics of ears of sweet maize, however, the use of the inoculation with Azospirillum brasilense and the application of thiamine as seed treatment is not recommended, since the vitamin in the doses studied inhibits the bacteria action and the it potential for the biological fixation of nitrogen.